2020
DOI: 10.3390/diseases8020012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Plantar Foot Stimulation in Parkinson′s Disease: A Scoping Review

Abstract: Background: Parkinson′s disease (PD) is the second most prevalent neurodegenerative disease in older individuals. Neurorehabilitation-based interventions such as those improving gait are crucial for a holistic approach and to limit falls. Several studies have recently shown that mechanical plantar foot stimulation is a beneficial intervention for improving gait impairment in PD patients. The objective of this scoping review is to evaluate the beneficial effects of this stimulation on gait parameters, and to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 84 publications
(126 reference statements)
0
11
0
Order By: Relevance
“…Thus, they are useful for implementing strategies to reduce the risk of falls which represents a major public health problem [50]. Recent reports suggest that IMUs, besides being useful in evaluating and to monitoring gait alterations in patients with neurodegenerative diseases such as Parkinson's disease [51][52][53], are useful for; patients with osteoarthritis [54], with benign paroxysmal positional vertigo, the most common peripheral vestibular disorder, leading to balance difficulties and increased fall risks [55] and walking disturbances in sarcopenic patients [56], they are also useful for gait event detection and analysis of gait alterations in patients with diabetes secondary to DPN [23,24,[27][28][29]31]. In spatiotemporal gait parameters recorded using a wearable sensor in patients with DPN, Kang et al showed that gait initiation steps and dynamic balance may be more sensitive than gait speed for detecting gait deterioration due to DPN [23], and Najafi et al demonstrated that gait alteration in patients with DPN is most pronounced while walking barefoot over longer distances [31].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they are useful for implementing strategies to reduce the risk of falls which represents a major public health problem [50]. Recent reports suggest that IMUs, besides being useful in evaluating and to monitoring gait alterations in patients with neurodegenerative diseases such as Parkinson's disease [51][52][53], are useful for; patients with osteoarthritis [54], with benign paroxysmal positional vertigo, the most common peripheral vestibular disorder, leading to balance difficulties and increased fall risks [55] and walking disturbances in sarcopenic patients [56], they are also useful for gait event detection and analysis of gait alterations in patients with diabetes secondary to DPN [23,24,[27][28][29]31]. In spatiotemporal gait parameters recorded using a wearable sensor in patients with DPN, Kang et al showed that gait initiation steps and dynamic balance may be more sensitive than gait speed for detecting gait deterioration due to DPN [23], and Najafi et al demonstrated that gait alteration in patients with DPN is most pronounced while walking barefoot over longer distances [31].…”
Section: Discussionmentioning
confidence: 99%
“…We assessed barefoot walking as footwear modify gait characteristics in patients with PD [33]. There is also evidence of the effect of plantar stimulation on parkinsonian gait [34] and specifically on FoG [35].…”
Section: Methodsmentioning
confidence: 99%
“…In response to this sensory feedback, corrective postural responses are evoked by lower limb neuromuscular system (Saeki et al, 2015;Tosovic et al, 2012). Some studies have highlighted the importance of peripheral sensory feedback applied to the plantar sole (Viseux et al, 2018(Viseux et al, , 2019Viseux, Martins, et al, 2020) and have improved clinical symptoms in Parkinsonian patients, including reduction in postural instability, through plantar sole stimulation (Brognara & Cauli, 2020;Viseux, Delval, et al, 2020). Given the linear relationship between the intensity of perceived pain and postural instability characterized by the velocity and amplitude of the centre of pressure displacement (Lihavainen et al, 2010;Ruhe et al, 2011Ruhe et al, , 2013Viseux et al, 2022), these results provide new clinical perspectives in the development of intervention strategies to manage postural instability and pain in patients with PD.…”
Section: Pharmacological Approachesmentioning
confidence: 99%